Forest typological structure of the stands in the Yunitsky National Botanical Reserve - Yurchenko, V. A. (Forestry and Forest Melioration, 2019)
Introduction Problems of combating drought and desertification have been relevant in the Steppe zone of Ukraine for many years. The key link of the adaptive-landscape arrangement of degraded agricultural lands is the agroforestry reclamation of territories. The Yunitsky National Botanical Reserve is located on the territory of the Luhansk Agroforestry Research Station (Belovodsky District, Luhansk Region). The Yunitsky National Botanical Reserve is one of the examples of ecological and economic optimization of the landscape by means of agroforestry methods. It is preserved on the territory of the botanical reserve that is an artificial forest tract, created at the end of the 19th century under the leadership of Dokuchaev. Growth of forest plantations has certain features in a dry, relatively warm Steppe’s climate that are determined by soil, hydrological and climatic conditions. They are climate aridity and its derivatives in particular. Materials and Methods The forest typological analysis was done for the forest stands based on the Production Association ‘Ukrderzhlisproekt’ Database, the fund and cartographic documents and other materials of permanent forest management. Data were processed following generally accepted in forestry and forest mensuration methods and methods of mathematical statistics. Results The Yunitsky National Botanical Reserve forest protective system covers all elements of the interfluve area relief. Ten forest types were determined based on the data of the forest management. The most common forest type is dry birch-and-oak fertile site that occupies 75.5% of the area. All the stands in the reserve were divided into 2 protection categories, namely the natural sanctuary – 552.9 ha (71.8%) and the anti-erosion forests – 217.4 ha (28.2 %). Maturing, mature and overmature age groups make 62.3% of the stands. The stands of 3rd and lower growth classes make 83.6%. The stands of vegetative origin cover 38.7%; the stands planted from acorns make 41.0% of the area. As for a health condition, most of the stands are severely weakened. Conclusions The causes of the stands’ die-back are weakening due to severe Steppe’s climatic conditions and then, on being weakened, trees become affected by root rot. The study showed that the most resistant tree species is common oak. 7 Figs., 6 Tables, 17 Refs.